Oppositions and lines of desire: Exploring the screenwriting approach of Claire Denis in a practice-based study - Dooley, Kath (Australian Association of Writing Programs, 2014)
In her twenty-five year career, French writer/director Claire Denis has produced close to a dozen feature films. Existing in the margins of mainstream cinema, Denis’s work includes disturbing and/or horrific films that explore the body as a site for identity formation, sexual debasement and transgressive urges. The majority of Denis’s films have been written in collaboration with co-writer Jean-Pol Fargeau, a process Denis describes as involving the ‘grafting’ of various elements into a coherent whole. This approach sees character and plot defined through the drafting of a ‘diagram of relations’, a form of construction that distances Denis from popular approaches to screenwriting undertaken in Australia. In this article I describe how I conducted a practical investigation of Denis’s approach by writing an original 25-minute screenplay (produced into a film in early 2012). This process was both a means of further enquiry into Denis’s thematic and practical concerns, and a creative outcome of my PhD research, which allowed for a reinvigoration and evaluation of my previous practice as screenwriter. The resulting script is a departure from my previous output, with a different approach to plot signifiers, conflict and the psychological representation of character. With self-reflexive examination and creative analysis, this paper explores the specifics of Denis’s approach and its impact when imported into my practice in an Australian context. Keywords: Claire Denis, screenwriting, the body